Analisis Financial Distress Menggunakan Regresi Data Panel - Annisa Ayu Lestari; Dwi Endah Kusrini (Politeknik Statistika STIS, 2021)
A company certainly wants to avoid conditions that can lead to bankruptcy, one of the conditions that can put a company in danger of bankruptcy is financial distress. This study aims to describe financial distress and find out the factors that affect financial distress in retail companies. This research was conducted on retail subsector companies in the period 2015 to 2019 using data panel regression method. Predictor variables are current ratio (CR), net profit margin (NPM), total assets turnover (TATO) and price to book value (PBV). The financial ratio used to measure financial distress is debt service coverage ratio (DSCR). The results of the analysis show that more companies in the non-primary consumer goods sector than in primary are in financial distress. NPM has a significant effect on DSCR, while CR, TATO and PBV had no significant effect on DSCR. The coefficient of determination of the selected model is 83,90%. Keywords: Financial Distress, Panel Data Regression, Retail